2019
DOI: 10.1111/age.12807
|View full text |Cite
|
Sign up to set email alerts
|

A splicing mutation in PHKG1 decreased its expression in skeletal muscle and caused PSE meat in Duroc × Luchuan crossbred pigs

Abstract: In recent years, Luchuan pigs in southern China have been used to produce high-quality meat by crossbreeding them with Duroc boars; however, PSE (pale, soft and exudative) meat was frequently reported in the crossbred pigs, and the underlying reason remains unknown. We excluded the possibility of the well-known causative mutations in RYR1 and PRKAG3 but identified the existence of an unfavorable allele of a splicing mutation (g.8283C>A) in PHKG1 in two Duroc boars and three Duroc 9 Luchuan crossbred pigs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Among these 63 candidate genes, the most famous one is PHKG1 , in which a splicing mutation (g.8283C > A) in Duroc pigs leads to increased glycolytic potential and rapid pH decline in meat [ 6 ]. In a previous study, we confirmed that the splicing mutation g.8283C > A is the causative mutation for the eQTL signal and that pigs that carry the mutant allele have a high risk of pale, soft, and exudative meat [ 30 ]. Other identified candidate genes that are of interest include NUDT7 , which was assigned to a QTL for meat color [ 47 49 ], and FADS2 and DGAT2 , which are involved in the regulation of lipid metabolism and fat deposition [ 50 – 52 ].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Among these 63 candidate genes, the most famous one is PHKG1 , in which a splicing mutation (g.8283C > A) in Duroc pigs leads to increased glycolytic potential and rapid pH decline in meat [ 6 ]. In a previous study, we confirmed that the splicing mutation g.8283C > A is the causative mutation for the eQTL signal and that pigs that carry the mutant allele have a high risk of pale, soft, and exudative meat [ 30 ]. Other identified candidate genes that are of interest include NUDT7 , which was assigned to a QTL for meat color [ 47 49 ], and FADS2 and DGAT2 , which are involved in the regulation of lipid metabolism and fat deposition [ 50 – 52 ].…”
Section: Discussionsupporting
confidence: 56%
“…Instead, for DNA-chip SNPs, we set a threshold of 19 for the median of the number of each genotype at each site to avoid an extreme distribution of genotypes. For ASE analysis with RNAseq data, Table 1 The overlap between eQTL analysis, ASE analysis and correlation analysis "Num_Het" represents the total number of observed heterozygotes, and "Num_ASE" means the number of heterozygotes that displayed ASE we applied the N-masking alignment strategy to eliminate allelic mapping bias and set filtering conditions for both total read counts (10) and allele-specific read counts (3), as well as the minimum sample size of heterozygotes (30) and the count of ASE heterozygotes (10), which ensured higher reliability. We found that 43.8% (378/863) of the trans-genes had a cis-eQTL on the same chromosome, such as SLC5A4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases associated with PHKG1 include glycogen storage disease ( Kishnani et al, 2019 ). Several studies have also demonstrated that PHKG1 is a strong candidate gene for meat quality traits in pigs ( Liu et al, 2019 ; Liu et al, 2020 ) and residual feed intake and feed conversion ratio in chickens ( Shah et al, 2016 ; Liu et al, 2018 ). Furthermore, a previous study demonstrated that the PHKG1 gene is a causative gene for meat quality traits in White Duroc × Erhualian F2 intercross and Sutai pigs, which could lead to a less active Phosphorylase Kinase ( PhK ) protein ( Ma et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duroc is a famous lean-type pig breed with high muscle mass and growth rate. However, there are remarkable phenotype differences in muscle mass, growth rate, back-fat thickness and intramuscular fat content between these two breeds [ 19 , 20 ]. Even so, the RNA editing sites contributing to the phenotype have rarely been reported in animals.…”
Section: Introductionmentioning
confidence: 99%